RELATIONSHIP OF LIPOPROTEINE-ASSOCIATED PHOSPHOLIPASE A2 WITH CORONARY AND CAROTID ATHEROSCLEROSIS IN KIRGIZ ETHNIC GROUP - A. G. Polupanov; Yu. N. Lomteva; T. A. Romanova; A. S. Dzhumagulova (Российский кардиологический журнал)
Aim. To study the association of the level (mass) of lipoproteine-associated phospholipase A2 with coronary and carotid atherosclerosis in the patients with essential arterial hypertension in Kirgiz ethnic group.Material and methods. Totally 52 patients studied with arterial hypertension (AH); mean age — 54,9±6,7, of those 26 men and 26 women. CHD, confirmed by exercise tests or coronary arteriography, had 19 patients, atherosclerosis of carotid arteries – 28. All patients underwent height measurement, weight and waist circumference, BP and HR measurement, also measurement of some biochemical values: fibrinogene level, sugar, creatinine of the blood and lipid profile (levels of total cholesterol, LDL, HDL and triglycerides). Measurement of LP-PLA2 was done using “PLAC” test by “DiaDexus” (USA) with immuneturbodimetry method “ELISA”. Duplex scanning of carotid arteries was done with Sequoia-512 by “Accuson” (USA).Results. There was direct correlation of LP-PLA2 correlation with the age (r=0,27; p<0,05), HDL concentration (r=0,30; p<0,05) and LDL (r=0,28; p<0,05) and negative association with triglycerides (r=-0,28; p<0,05). Significant differences by gender in LP-PLA2 were not found (p>0,05). Patients with CHD had higher level oftotal cholesterol (5,64±0,97 mmol/l vs. 5,23±1,33 mmol/l, р=0,057), LDL (3,63±0,89 mmol/l vs. 3,16±0,98 mmol/l, p<0,01), and the mass of LP-PLA2 (296±70 ng/ml vs. 237±76 ng/ml, p<0,005) comparing to the patients with EH and CHD. In multifactorial regression analysis it was shown that only concentration of LP-PLA2 independently associated with CHD among native inhabitants of the Republic (β=0,66; p<0,001). We did not found association of LP-PLA2 with presence and prominence of carotid atherosclerosis and carotid intima-media thickness (p>0,05).Conclusion. In Kirgiz ethnic group there is association of LP-PLA2 with CHD, but not with carotid atherosclerosis.